Probiotic Usage in Food Allergy Atopic Dermatitis Children. A Literature Review - wijaya, dhani - (Brawijaya University, 2019)
Food allergy is a health problem that commonly occurs among children. One of the clinical manifestations of food allergy is atopic dermatitis. Food allergies are pathological reaction involving the immune system. Atopic dermatitis (AD) is related to the immune system. The immune system is affected by intestinal microbes. Probiotics are substances that can regulate the immune system for the digestive tract, particularly in the intestines. Probiotics have a therapeutic effect on several illnesses, specifically those related to the immune system. The aim of this review is to discuss knowledge related to the usage of probiotics for the therapy of atopic dermatitis caused by food allergies in children. This literature review focused on the mechanism of actions of probiotics in children with atopic dermatitis caused by food allergy.Â